The association of diet quality and physical activity with cardiovascular disease and mortality in 85,545 older Australians: A longitudinal study - Ding Ding; Joe Van Buskirk; Stephanie Partridge; Philip Clare; Edward Giovannucci; Adrian Bauman; Nicole Freene; Robyn Gallagher; Binh Nguyen (Elsevier, 2024)
Background: A quality diet and an active lifestyle are both important cornerstones of cardiovascular disease (CVD) prevention. However, despite their interlinked effects on metabolic health, the 2 behaviors are rarely considered jointly, particularly within the context of CVD prevention. We examined the independent, interactive, and joint associations of diet and physical activity with CVD hospitalization, CVD mortality, and all-cause mortality. Methods: CVD-free Australian participants aged 45-74 years (n = 85,545) reported physical activity, diet, sociodemographic, and lifestyle characteristics at baseline (2006-2009) and follow-up (2012-2015), and data were linked to hospitalization and death registries (03/31/2019 for CVD hospitalization and all-cause mortality and 12/08/2017 for CVD mortality). Diet quality was categorized as low, medium, and high based on meeting dietary recommendations. Physical activity was operationalized as (a) total moderate-to-vigorous physical activity (MVPA) as per guidelines, and (b) the composition of MVPA as the ratio of vigorous-intensity physical activity (VPA) to total MVPA. We used a left-truncated cause-specific Cox proportional hazards model using time-varying covariates. Results: During a median of 10.7 years of follow-up, 6576 participants were admitted to the hospital for CVD and 6581 died from all causes (876 from CVD during 9.3 years). A high-quality diet was associated with a 17% lower risk of all-cause mortality than a low-quality diet, and the highest MVPA category (compared with the lowest) was associated with a 44% and 48% lower risk of CVD and all-cause mortality, respectively. Multiplicative interactions between diet and physical activity were non-significant. For all outcomes, the lowest risk combinations involved a high-quality diet and the highest MVPA categories. Accounting for total MVPA, some VPA was associated with further risk reduction of CVD hospitalization and all-cause mortality. Conclusion: For CVD prevention and longevity, one should adhere to both a healthy diet and an active lifestyle and incorporate some VPA when possible.